Karakteristik Alat Uji Sistem Pendorong pada Autonomous Underwater Vehicle (AUV) - Muhammad Tadjuddin (Jurnal Teknik Mesin Unsyiah, 2012)
Aceh marine area has many potential resources that need to be explored, studied, and conserved. These activities require a suitable mean that has capability to bring data collection and observation tools into the seabed. One of the means that can carry out these jobs is the AUV (Autonomous Underwater Vehicle). AUV has an ability to dive without any supporting cables from the surface. It can be programmed to do the required task in the seabed. One of the most important parts on the AUV is the thruster system, a component that provides the thrust force. A thruster is a mechatronic device consists of power source (battery), motor controller, electric motor, and propeller as the main thrust component. A defect in the thruster design will result in the failure of the AUV thus the design of thruster is critical in an AUV unit. In this research, an experiment apparatus was design and fabricated in order to measure the performance of a thruster. The measurement includes the thrust force, the power consumption, and the total effective working time. The proposed experiment apparatus is expected to assist the design stage of the AUV before fabrication in order to minimize the failure caused by defect in the thruster system.